ARE WE PREPARED ENOUGH? A CASE STUDY OF CHALLENGES IN ONLINE LEARNING IN A PRIVATE HIGHER LEARNING INSTITUTION DURING THE COVID-19 OUTBREAKS: ARE WE PREPARED ENOUGH? A CASE STUDY OF CHALLENGES IN ONLINE LEARNING IN A PRIVATE HIGHER LEARNING INSTITUTION DURING THE COVID-19 OUTBREAKS - Yusuf, Bibi Noraini (Advances in Social Sciences Research Journal, 2020)
Online learning is a learning methodology implemented during the recent COVID-19 outbreaks.Lecturers and students need to use appropriate online platformsarising from the Movement Control Order (MCO) restrictions with effect from March 18, 2020, in Malaysia. In essence, the MCO prohibits Malaysians from attending to or organizing mass events or public gatherings, and where public and private educational institutions are concerned, they are not allowed to conduct any classesin situ. The only possible continuation of classes is via online learning. This case study had two research objectives: 1) Whatwere the challenges faced by educators when implementing online learning? and 2) How to overcome these challenges faced by educators in online learning? This study had applied the qualitative approach method, where researchers had distributed surveys, through a google platform, to a total of 20 educators. The results showed six (6) major challenges faced by educators in online learning, these being 1) students were less focused on online learning; 2) the platform/medium of learning was not satisfactory; 3) students left behind learning tools such as books and laptops in residential colleges; 4) students' internet access was less satisfactory to the extent that the lectures had to be extended from the actual time allocated; 5) educators' unstable internet access which disrupted the momentum of teaching; and 6) students did not attend the online courses. There were four (4) means to overcome these challenges 1) institutions to provide more comprehensive and e-learning platforms for online learning; 2) internet access for educators and students should be good to ensure smooth and uninterrupted online classes; 3) providing workshops or training programs on management of online classes for educators; and 4) for courses involving mathematical computation, in addition to a more suitable platform for teaching, the student population per group to be small in size to accommodate 10 educators while teaching. The results of this study shall benefit the management of private higher learning institutions and educators involved in online learning.